2017
DOI: 10.1038/s41598-017-02800-2
|View full text |Cite|
|
Sign up to set email alerts
|

miR-15a/miR-16 down-regulates BMI1, impacting Ub-H2A mediated DNA repair and breast cancer cell sensitivity to doxorubicin

Abstract: The B-lymphoma Moloney murine leukemia virus insertion region-1 protein (BMI1) acts as an oncogene in various cancers, including breast cancer. Recent evidence suggests that BMI1 is rapidly recruited to sites of DNA double strand breaks where it facilitates histone H2A ubiquitination and DNA double strand break repair by homologous recombination. Here we show that miR-15a and miR-16 expressionis decreased during the initial period after DNA damage where it would otherwise down-regulate BMI1, impairing DNA repa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 58 publications
2
24
0
Order By: Relevance
“…miR‐16 directly targets BMI‐1, which is a repressor of p16 INK4A and p19 INK4D cell cycle inhibitors . Another study reported that miR‐16 induces G2/M arrest through suppression of BMI1 in MDA‐MB‐231 cells . Considering the inhibitory effect of miR‐302 cluster on BMI‐1, it can be expected that transfection with miR‐16 may enhance this effect and lead to a stronger cell cycle arrest as we detected.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…miR‐16 directly targets BMI‐1, which is a repressor of p16 INK4A and p19 INK4D cell cycle inhibitors . Another study reported that miR‐16 induces G2/M arrest through suppression of BMI1 in MDA‐MB‐231 cells . Considering the inhibitory effect of miR‐302 cluster on BMI‐1, it can be expected that transfection with miR‐16 may enhance this effect and lead to a stronger cell cycle arrest as we detected.…”
Section: Discussionsupporting
confidence: 65%
“…62,63 Another study reported that miR-16 induces G2/M arrest through suppression of BMI1 in MDA-MB-231 cells. 64 Considering the inhibitory effect of miR-302 cluster on BMI-1, 12 it can be expected that transfection with miR-16 may enhance this effect and lead to a stronger cell cycle arrest as we detected. In both MDA-miR-302/367 and SK-miR-302/367 cells, transfection with miR-16 mimic led to CDKN1A overexpression.…”
Section: Discussionmentioning
confidence: 56%
“…In addition, miR‐195 , a member of the miR‐15/miR‐16 family, has been shown to inhibit glioma cell proliferation and to modulate acquired resistance to TMZ . Moreover, members of the miR‐15/miR‐16 family have been linked to resistance against other drugs, including cisplatin, doxorubicin and 5‐fluorouracil . Therefore, we addressed potential effects of miR‐16‐5p overexpression on the response of glioma cells to irradiation and TMZ.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the pivotal role of miRNAs in cancer initiation, progression, and metastasis . miR‐34a and miR‐16 are two tumor suppressor miRNAs associated with the development of breast cancer (BC) …”
Section: Introductionmentioning
confidence: 99%